The effect of the implementation of the international code of marketing of breast-milk substitutes on child mortality in Ghana and Tanzania - Juliana Lima Constantino; Stefan Pichler; Lybrich Kramer; Regien Biesma (Cambridge University Press, 2024)
Abstract Objective: The International Code of Marketing of Breast-Milk Substitutes is an important instrument to protect and promote appropriate infant and young child feeding and the safe use of commercial milk formulas. Ghana and Tanzania implemented the Code into national legislation in 2000 and 1994, respectively. We aimed to estimate the effects of the Code implementation on child mortality (CM) in both countries. Setting: The countries analysed were Ghana and Tanzania. Participants: For CM and HIV rates, data from the Institute for Health Metrics and Evaluation from up to 2019 were used. Data for income and skilled birth rates were retrieved from the World Bank, for fertility from the World Population Prospects, for vaccination from the Global Health Observatory and for employment from the International Labour Organization. Design: We used the synthetic control group method and performed placebo tests to assess statistical inference. The primary outcomes were CM by lower respiratory infections, mainly pneumonia, and diarrhoea and the secondary outcome was overall CM. Results: One-sided inference tests showed statistically significant treatment effects for child deaths by lower respiratory infections in Ghana (P = 0·0476) and Tanzania (P = 0·0476) and for diarrhoea in Tanzania (P = 0·0476). More restrictive two-sided inference tests showed a statistically significant treatment effect for child deaths by lower respiratory infections in Ghana (P = 0·0476). No statistically significant results were found for overall CM. Conclusion: The results suggest that the implementation of the Code in both countries had a potentially beneficial effect on CM due to infectious diseases; however, further research is needed to corroborate these findings.